LAKON SUBALI LENA SAJIAN ENTHUS SUSMONO DALAM PERSPEKTIF ETIKA: RELEVANSINYA DENGAN AJARAN MORAL SYAIKH MAULANA ILYAS - , Muh. Mukti, S.Kar.N.Sn., Prof. Dr.Lasiyo, MA. MM. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research entitled: The Story SubaliLena Serving Enthus Susmono in Perspective Ethics: Itâs Relevance with Shaikh Maulana Ilyasâ Moral Teachings. The research is motivated by the phenomenon of fame mastermind Enthus Susmana is thick with Islamic nuance in every performer. Phenomenon was tested relevance with preaching the teachings of Shaikh Maulana Ilyas . The research objective was formulated: first describe wayang performance by Enthus Susmana with the story Subali Lena. Second perform a critical analysis of the ethical values contained in the he story SubaliLena Enthus Susmana dish. Third reflecting the relevance of ethical values in the story SubaliLena Enthus Susmana dish with giving spirit Islam of Shaikh Maulana Ilyas for improvementmoral community and the wayang preservation. This research, is philosophy research. The material object in this research is the performance of wayang kulit purwa story the Subali Lena by Enthus Susmono. The formal object in this research is ethics. This research is descriptive-qualitative philosophy research. The main methods used in the analysis is hermeneutics and heuristics. General methodical hermeneutics elements used in the analysis is verstehen, descriptions, and reflection. The following results. First, The story SubaliLena covering all aspects of essentially still on track grip (classical wayang tradition) , there are only a few shifts that are not flashy like form of color , costumes puppeteer , musician and puppeteer expressions are adopted Islam , such as taking reference Al Quran and Hadist. Second , The story Subali Lena contain the valuable ethical teachings as reflected in puppet dialogue. The teachings are about the conscience, rights and obligations, freedom and responsibility and justice. Third , the value of preaching the teachings contained in the The story SubaliLena is very relevant to the teaching mission of Shaikh Maulana Ilyas, a scholar and thinker exemplary preaching the teachings of Islam which many Muslims in Indonesia. Therefore the value of in deployment the The story SubaliLena relevant moral community improvement efforts and the wayang preservation.